Effect of acupuncture on post-stroke dysphagia: a randomized controlled trial - Bai, Lin; Cheng, Hongliang; Hu, Peijia; Wang, Qingqing; Shilin, Zhang; Shen, Zhiqiang; Xu, Fangyuan; Su, Xingxing; Zhang, Yiting (Frontiers in Neurology, 2024)
Post-stroke dysphagia (PSD) is associated with various complications that increase morbidity and mortality rates. Acupuncture has been used extensively in China to treat these complications; however, its therapeutic efficacy remains uncertain. We therefore aimed to study the clinical effects of acupuncture on PSD. Methods: Patients (n=101) were randomly divided into acupuncture (n=50) and rehabilitation training control (n=51) groups based on the treatment used. Both groups were treated once daily, 6 days a week, for a total of 4 weeks. Pulse oxygen saturation (SpO2) and standardised swallowing assessment (SSA) were performed before the intervention, 2 weeks into treatment, after the intervention (4 weeks post-intervention), and at a 6-month follow-up (28 weeks). The levels of haemoglobin (Hb) and albumin (ALB), and 5-hydroxytryptamine (5-HT) and dopamine (DA) were measured before the intervention, 2 weeks into treatment, and after the intervention (4 weeks), as nutrition and swallowing function indices, respectively. Results: Following the intervention, significant differences were observed between the acupuncture and control groups. The acupuncture group exhibited considerably superior enhancements in SpO2 and SSA scores at 4 weeks (P<0.001). Moreover, this group demonstrated significantly greater improvements in Hb, ALB, 5-HT, and DA values 4 weeks post-treatment (P<0.001). However, sex-based differences were not observed (P ＞0.005). Conclusion: Acupuncture treatment can improve the swallowing function and nutritional status of patients with PSD, and increase the levels of 5-HT and DA. These findings strongly support the efficacy of acupuncture as a therapeutic intervention in patients with PSD.Clinical Trial Registration: ChiCTR2100052201.